2016
DOI: 10.31018/jans.v8i3.980
|View full text |Cite
|
Sign up to set email alerts
|

Survey, documentation and identification of entomofauna of cocoa, Theobroma cacao L. in major cocoa growing regions of South India

Abstract: Survey, monitoring and documentation of entomofauna of cocoa was carried out in three cocoa growing states viz., Tamil Nadu, Kerala and Andhra Pradesh during 2014-2015. Results revealed that a total number of 23 species of insect pests and 13 species of natural enemies were documented and identified. Among the insect pests, 14, 2 and 7 species were sucking pests, borers and defoliators, respectively. Among the natural enemies, 7 species of predators and 6 species of parasitoids were documented and identified o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results of this study were different from another study. Srinivasnaik et al (2016) found 23 herbivores and 13 species as natural enemies in South India. Among herbivores, 14 species are classified as sucking pests, two as borers, and seven species are classified as defoliators.…”
Section: Abundance and Species Richness Of Insectmentioning
confidence: 99%
“…The results of this study were different from another study. Srinivasnaik et al (2016) found 23 herbivores and 13 species as natural enemies in South India. Among herbivores, 14 species are classified as sucking pests, two as borers, and seven species are classified as defoliators.…”
Section: Abundance and Species Richness Of Insectmentioning
confidence: 99%